(untitled) (Research, Society and Development, 2022)
This study aimed to identify podiatric care performed in the care of elderly people with diabetes mellitus to prevent ulcerations. This is an integrative review carried out in the MEDLINE, CINAHL, Science Direct, Web of Science, SCOPUS, IBECS and LILACS databases. Initially, 1,572 articles were identified, which were submitted to the research eligibility criteria, resulting in a final sample of three articles. The main podiatric care undertaken in elderly people with diabetes was evidenced: proper nail clipping performed by a professional; management of pain and deformities; footwear prescription; treatment of onychomycosis with laser; foot inspection; evaluation of foot pulses and protective sensitivity test with 10g monofilament, vibratory sensitivity with the tuning fork 128 Hz, pain sensitivity, Achilles reflex and vibration perception threshold. Much of the care is already recommended by national and international guidelines on the subject, emphasizing the absence of other care performed in clinical practice. It is concluded that it is necessary to advance in the discussion of podiatric care in elderly people with diabetes in the perspective of producing more studies on the subject of good methodological quality for clarification and theoretical basis of practices in clinical podiatry that contribute to the reduction of morbidity and mortality associated with the foot. diabetic.